PERAN KEPALA SEKOLAH DALAM MENGELOLA SARANA DAN PRASARANA - Awalia , Rubi (ILJ: Islamic Learning Journal, 2023)
The purpose of this study is to determine the importance of the role of school principals in managing educational facilities and infrastructure. This research is a literature research with documentary research method and the analysis uses content analysis. The results of this study indicate the importance of the principal's role in managing facilities and infrastructure. Learning facilities are all devices, equipment, materials and furniture that can be moved directly used in learning at school. While infrastructure is a basic facility that indirectly supports the learning process in schools such as fields, parks, school yards and so on. The role of the principal in managing facilities and infrastructure is the principal as a manager and principal as an administrator.